"I took the road less traveled, and that has made all the difference": Making a case for high‐dose therapy and autologous stem cell transplantation in elderly patients with newly diagnosed multiple myeloma. Issue 22 (10th August 2021) - Nooka, Ajay K.; Joseph, Nisha S.; Lonial, Sagar
Abstract : Lay Summary: Elderly patients with myeloma derive benefits from transplantation similar to those for younger patients. Age should not be the sole criterion for determining transplant eligibility. Performance status assessment and other tools for assessing comorbidities such as the Charlson comorbidity score may potentially help in determining transplant eligibility and will allow us to move away from our heavy reliance on numerical age. Abstract : Elderly patients with myeloma derive benefits from transplantation similar to those for younger patients. Age should not be the sole criterion for determining transplant eligibility. Performance status assessment and other tools for assessing comorbidities such as the Charlson comorbidity score may potentially help in determining transplant eligibility and will allow us to move away from our heavy reliance on numerical age.